Public Participation And Political Literacy In Regional Head Elections (Pilkada) In Kamal Village, Ogan Ilir Regency : Penelitian - Achmad Rofiqo Ridho; Adellah Adellah; Maria Immaculata Yovita Adventy; Naurah Athaya; Jumroh Jumroh (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Political participation and literacy at the village level remain challenges, particularly in rural areas with limited access to information and political education. In Kamal Village, a low understanding of election stages and weak digital literacy hampered the quality of participation in the Regional Head Election. The program utilized a qualitative participatory approach involving residents, election organizers, and community leaders. Data was collected through interviews, observation, documentation, and group discussions, then analyzed using triangulation. The program increased residents' understanding of election stages, voter rights and obligations, and the role of electoral institutions. Digital education through WhatsApp, infographics, and short videos accelerated information dissemination. Resident participation increased in voter list verification, political discussions, and village election activities. The political culture shifted toward participatory participation. Community service in Kamal Village effectively increased political literacy and election participation through a combination of direct involvement and the use of simple digital media.